Perbedaan Pengaruh Penerapan Model Pembelajaran Course Review Horay Dan Quantum Teaching Dilihat Dari Hasil Belajar Matematika Siswa Kelas 3 SD - Mesti Fajar Romadhoni; Stefanus C. Relmasira (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
Mathematics is a numerical study that has a strong relation to countings. Learning method of Course Review Horay and Quantum Teaching could arise students’ enthusiasm to get good grades. Purpose of this study was to observe differences in Mathematics learning result using learning model of Course Review Horay and Quantum Teaching. This was an experiment research type Quasi Experiment design Nonequivalent Pretest-Postest Control Grup Design. Test result between group of experiment and control showed there was an equivalent. Technic of collecting data was through observation and test. Participants of this study were students 3A of SD Kristen Satya Wacana as Experiment group and students 3B of SD Negeri Salatiga 6 as Control group. Data was analysed using T-test with Independent Sample t-test technique with 5% significance level (α = 0,05). The result showed that there was significant difference in applying Course Review Horay learning and Quantum Teaching learning model. It was proven in t-test posttest showed t-calculate was -4,642 with sig.(2-tailed) adalah 0,000 < 0,05 to df 48 obtained t table value = 2,011 with t-test gain score which showed the value of t calculate was -2,687 with sig.(2-tailed) 0,010 < 0,05 to df 48 obtained t table = 2,011.